2014
DOI: 10.1016/j.nlm.2013.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Human fear extinction and return of fear using reconsolidation update mechanisms: The contribution of on-line expectancy ratings

Abstract: Disruption of the reconsolidation of conditioned fear memories has been suggested as a non-pharmacological means of preventing the return of learned fear in human populations. A reconsolidation update paradigm was developed in which a reconsolidation window is opened by a single isolated retrieval trial of a previously reinforced CS+ which is then followed by Extinction Training within that window. However, follow-up studies in humans using multi-methods fear conditioning indices (e.g., fear-potentiated startl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 61 publications
(127 reference statements)
3
54
1
1
Order By: Relevance
“…Few studies in our meta-analysis utilized expectancy ratings, preventing direct analysis of this variable. However, some have hypothesized that the act of completing expectancy ratings during acquisition trials encourages participants to identify the contingency between the CS and US (Warren et al, 2014). Here we found that the use of expectancy ratings significantly moderated the effects of post-retrieval extinction on return of fear in humans, with more favorable outcomes for studies that did not involve expectancy ratings, suggestive of greater benefit for non-hippocampal dependent memories.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies in our meta-analysis utilized expectancy ratings, preventing direct analysis of this variable. However, some have hypothesized that the act of completing expectancy ratings during acquisition trials encourages participants to identify the contingency between the CS and US (Warren et al, 2014). Here we found that the use of expectancy ratings significantly moderated the effects of post-retrieval extinction on return of fear in humans, with more favorable outcomes for studies that did not involve expectancy ratings, suggestive of greater benefit for non-hippocampal dependent memories.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, erasure of fear memories through reconsolidation has been shown to depend on prediction error as captured by US expectancy ratings (Sevenster et al, 2013) and some evidence could even suggest that these disruption of reconsolidation effects are more pronounced with concurrent US expectancy ratings (Warren et al, 2014). Thus, reduction of FPS through disruption of reconsolidation may not be as independent of expectancies and SCRs as some studies suggest.…”
Section: Contingency Reversal 27mentioning
confidence: 98%
“…In summary, the findings of Schiller et al (2010), Agren et al (2012), and Björkstrand et al (2015) ., 2012), others have found the critical retrieval manipulation to be ine ective (Fricchione et al, 2016;Golkar et al, 2012;Kindt & Soeter, 2013;Klucken et al, 2016;Meir Drexler et al, 2014;Soeter & Kindt, 2011;Warren et al, 2014). Attempts to replicate the original demonstration of reconsolidation-extinction in rats (Monfils et al, 2009) replications, it can be di cult to ascertain whether a putative reconsolidation process is being modulated by subtle theoretically-irrelevant procedural di erences, or theoretically-relevant 'boundary conditions' (Auber et al, 2013;Haaker et al, 2014 Since its (re)birth a decade and a half ago (Nader et al, 2000a;Przybyslawski & Sara, 1997;Sara, 2000a), the theory of reconsolidation has been buoyed by considerable empirical attention and theoretical excitement (Alberini, 2011;Besnard et al, 2012;Dudai, 2004;Nadel & Land, 2000;Nader et al, 2000b;Nader & Hardt, 2009;Nader, 2015; 21 Note that Agren et al and Bjorkstrand et al also reported correlations between blood oxygen level dependent (BOLD) activity in the amygdala and the behavioural return of fear measure.…”
Section: Cs = Plus/minusmentioning
confidence: 99%